Patterns of Nonarticular Rheumatism in a Rural Area of Bangladesh - Hasan, M Masudul; Haq, Syed Atiqul; Choudhury, Minhaj Rahim; Islam, Md Nazrul; Das, Aparna; Banik, Gobinda; Mondal, Mohammed Tawhidul Islam; Ali, Md Rustom (Journal of Medicine, 2012)
Objectives: Estimate the prevalence of nonarticular (soft tissue) rheumatism in a rural population of Bangladesh. Methods: The survey was carried out in eight villages of Sonargaon upazila of Narayanganj district about 30 kilometers from Dhaka. All subjects of both genders (5217) of ?15 years old of 8 villages were evaluated. Door to door survey was done to cover missing cases. Trained field workers identified subjects with musculoskeletal pain using Bengali version of the COPCORD (Community Oriented Program for the Control of Rheumatic Disease) questionnaire. Positive respondents were examined by trained internist and rheumatologists for definite non articular rheumatic disorders. COPCORD guideline was used for diagnosis. Results: MSK pains (positive respondent) were 1260 (24.2%) in out of 5217 (male 2556, female 2661). Among of them definite soft tissue rheumatic diseases were identified in 439 (male 102 and female 337). Major occupations were house wives (54.7), weavers (18%), and peasants (5.1%). Definite point prevalence of nonarticular rheumatism was 8.41% (male 3.7%, female 11.09%). The most common diseases were fibromyalgia (3.95%), repetitive strain injury (2.3%), nocturnal muscle cramp (0.59%), myofascial neck pain (0.48%), planter fasciitis (0.46%). Conclusion: Prevalence of nonarticular rheumatism is common in this rural community. Fibromyalgia is the leading disease. DOI: http://dx.doi.org/10.3329/jom.v13i2.12752 J Medicine 2012; 13 : 165-169